Política de formação continuada de professores: a repercussão do Programa Pró-Letramento no trabalho de professores de escolas públicas - LUZ, Iza Cristina Prado da (Universidade Federal do Pará, 2012)
This dissertation is on the Policy of Continuing Education of teachers in Brazil, having as its object of study, the Pró-Letramento, a continuing education program for public school teachers, in the distance (blended), which aims to improve the learning reading / writing and math in early grades of elementary school conducted by the MEC, in partnership with universities that comprise the National Network of Continuing Education of Teachers and education systems. The research problem consists of the following concern: The Pró-Letramento is part of current educational policy of casualization, intensification of teachers 'work and teachers' accountability for the results of educational systems? This investigation was guided by the following motivating questions: The Pró-Letramento has contributed to improvement of teaching? What conceptions of continuing education and teaching are present in this educational policy? The Pró-Letramento has enhanced the accountability of teachers for student performance? The aim was to analyze the impact of the Pró-Letramento in the work of teachers who work in public schools, who participated or are participating in continuing education offered by this program during the period between the years 2008 to 2011, in Belém pole with basis at present for the discussion of educational policies in Brazil. As specific objectives, this research sought to identify whether the academic program Pró- Letramento integrates a policy of enhancing the teaching that aims to improve working conditions, remuneration and professional, to investigate the design of continuing education that is present in this educational policy, if restricted the knowledge or wider in order to provide an understanding of the social context in which professional activities and processes, verify that the Pró-Letramento has enhanced the accountability of teachers for student performance, and the school system or the intensification of teaching. The procedures consisted of Theoretical and methodological literature, document analysis and field research, by conducting semi-structured interview. For the data analysis was performed content analysis. This research pointed out the main results, based on the theoretical part listed in the report and the teachers interviewed, the in-service training and distance in the basilar proposals for government programs have been presented as a training that is developed lighter, just based theory, discrete and decontextualized implying debts to professional performance of teachers and teacher students that the teachers of the Pró-Letramento does not have relied on adequate working conditions, career, salary and continuing education. Based on the end, it appears that there is a need for an effective training policy capable of forming a professional with ability to understand social processes and relate them to the context of their professional practice, and thus a break with policy of teacher education, based on a utilitarian perspective and individualizing continuing education of teachers and separated from the guarantee of appreciation of the teaching and proper working conditions.